Penelitian korelasi Uji Tanah Hara Phosphorus Di Tanah Andisol Untuk Kedelai (Glycine max,L.) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Soybean has a very high prospect to be developed In Andlsols of upland soils if supported by suitable varieties and proper soil management. Research aimed at selecting extraction method and determining soil P critical level for soybean on Andisols has been conducted at laboratory and green house of Indonesian Soil Research Institute In Bogor by using soil sample taken from Karo, North Sumatera. The experiment used single location approach with two steps of activities. The first step was to make artificial soil P status by adding P: 0 X (very low), 1/.4 X (low), ~ X (medium), ¥.t X (high), and X (very high soil P status), where X was amount of P required to attain 0.2 ~ PIt In soil solution (Fox and Kamprath, 1970). The second step conducted after two months Incubation was P treatment in each artificial soil P status by using P fertilizer: 0,10,20,40, and 80 kg P/ha from SP-36 and replicated 3 times. Before application of P fertilizer at the second step, soil samples from each soil P status were taken to analyze the concentration of P with HCI 25 %, Bray I, Bray II, Truog, Mehlich, Olsen, and Colwell. The result showed that Truog and Olsen could be used to estimate P fertilizer requirement for soybean on Andisols. According to Cate and Nelson (1971) procedure, a critical level of soil P extracted by Truog was 250 ppm P20S, whereas the critical level extrakted by Colwell was 80 ppm PzOs.